Insulin signaling as a mechanism underlying developmental plasticity: the role of FOXO in a nutritional polyphenism. - Emilie C Snell-Rood; Armin P Moczek (PLoS ONE)
We investigated whether insulin signaling, known to mediate physiological plasticity in response to changes in nutrition, also facilitates discrete phenotypic responses such as polyphenisms. We test the hypothesis that the gene FOXO--which regulates growth arrest under nutrient stress--mediates a nutritional polyphenism in the horned beetle, Onthophagus nigriventris. Male beetles in the genus Onthophagus vary their mating strategy with body size: large males express horns and fight for access to females while small males invest heavily in genitalia and sneak copulations with females. Given that body size and larval nutrition are linked, we predicted that 1) FOXO expression would differentially scale with body size (nutritional status) between males and females, and 2) manipulation of FOXO expression would affect the nutritional polyphenism in horns and genitalia. First, we found that FOXO expression varied with body size in a tissue- and sex-specific manner, being more highly expressed in the abdominal tissue of large (horned) males, in particular in regions associated with genitalia development. Second, we found that knockdown of FOXO through RNA-interference resulted in the growth of relatively larger copulatory organs compared to control-injected individuals and significant, albeit modest, increases in relative horn length. Our results support the hypothesis that FOXO expression in the abdominal tissue limits genitalia growth, and provides limited support for the hypothesis that FOXO regulates relative horn length through direct suppression of horn growth. Both results support the idea that tissue-specific FOXO expression may play a general role in regulating scaling relationships in nutritional polyphenisms by signaling traits to be relatively smaller.